Knowledge and Attitude Regarding Cervical Cancer Screening in Women attending Obstetrics and Gynaecological Opd at Birat Medical College Teaching Hospital - Mahato, Raj Deb; Deo, Amit; Pokharel, Hanoon (Birat Journal of Health Sciences, 2020)
Introduction: Cervical cancer is the most common Gynaecological cancer in Nepal which is preventable if appropriate screening and prevention measures are employed. Considerable reduction in cervical cancer incidence and cervical cancer related deaths can be achieved by effective screening. However, lack of knowledge and awareness can result in underutilization of the preventive measures. Objectives: The objective of this study was to assess the knowledge and attitude regarding cervical cancer screening in women visiting Obstetrics and Gynaecology OPD at tertiary care Hospital in Eastern Nepal. Methodology: A cross-sectional questionnaire-based study was conducted in Obstetrics and Gynaecology outpatient department of Birat Medical College Teaching Hospital from 1 January 2019 to 31 December 2019. Women were enrolled in the study by convenient sampling methods. Structured questionnaire was used to collect the data. The collected data was entered in Microsoft excel and analyzed by using SPSS version 22. Results: Among 374 participants, the mean age was 31.13 years. More than three fourth (89.6%) of participants were literate. Regarding occupation, 89.8% of participants were housewives, and 82.9 % of participants were married. As per the findings, only 43.27 % of participants i.e. less than the mean, had adequate knowledge of cervical cancer and its screening. 65.50 % of participants had a negative attitude towards cervical cancer screening. Literate participants had good knowledge and positive attitude regarding cervical cancer screening than illiterate participants (P value less than 0.05). Conclusion Considerable proportions of participants had inadequate knowledge and negative attitude regarding cervical cancer screening in Gynaecological patients visiting tertiary care Hospital in Eastern Nepal.